Under-Enforcement of Corporate Criminal Liability: Indonesia’s Normative Commitment and Systemic Impunity - Tumian Lian Daya Purba; Silvester Magnus Loogman Palit; Ali Rahman; Yassine Chami (Jurnal Ilmiah Kebijakan Hukum, 2026)
Corporate criminal liability has been progressively recognised in Indonesia through sectoral legislation, procedural regulations, and the new Criminal Code, indicating a strong formal commitment to hold corporations accountable for corruption and other economic crimes. In practice, however, corporations are still rarely prosecuted, and enforcement remains heavily focused on individual offenders. This article examines the gap between “law in the books” and “law in action” and argues that the persistent under-enforcement of corporate criminal liability has produced a pattern of systemic impunity for corporate actors. Using a normative juridical method combined with case-law analysis and secondary empirical materials, the study reconstructs the legal framework, maps enforcement patterns in corruption, banking, environmental, tax and labour sectors, and identifies doctrinal, procedural, institutional, and political–economic factors that discourage prosecutors and judges from pursuing corporate defendants. The novelty of this article lies in treating under-enforcement itself as the central analytical problem and offering an integrated explanatory framework that connects legal design, institutional capacity, and political–economic incentives. The article concludes by proposing reforms to clarify liability standards, strengthen evidentiary and procedural tools, enhance institutional capacity and coordination, and insulate enforcement from undue corporate influence so that corporate criminal liability can function as an effective mechanism of accountability rather than merely a symbolic commitment